Studi Penyebab Keterlambatan Penyelesaian Proyek-Proyek Infrastruktur di Kota Binjai - SURI KENCANA (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2019)
Binjai Municipality, through the Public Works and Layout Agency of Binjai, prepares its budget each year to town development through building and infrastructure construction projects. As what happens in other towns in Indonesia, about 60% until 70% of construction projects at Binjai undergo lateness. The objective of the research is to study and find out the causes of lateness which usually occurs in implementing construction projects, to analyze the most dominant cause, to give input/suggestions of how to prevent the lateness in the future. Since the population was not homogenous, the samples were taken by using proportional stratum random sampling technique. The data were gathered by using questionnaires on the causes of lateness in 7 categories and 35 variables. There were 15 construction projects with 32 respondents with 15 respondents as the project owners, 12 respondents as the constructors, and 5 respondents as the supervisors/consultants. The price of construction materials which are rapidly increasing with the percentage of 42% should be heeded. According to the project owners, the lateness is caused by disturbance of the peace. The contractors argue that it is caused by the price of materials which is rapidly increasing. Good and mature planning should be in accordance with the needs and should be able to be understood and applied in the field in order to get accurate construction with cheap financing so that in the future construction projects can be completed punctually according to what has been planned. Keywords: Causes of Lateness, Construction Projects, Interest Index